STUDI TINGKAT PENGETAHUAN MAASYARAKAT TENTANG PENGGUNAAN ANTIBIOTIK DI KELURAHAN MALAWILI, KECAMATAN AIMAS, KABUPATEN SORONG - Hendra Herman; Irma Santi; Intan Puspita Ramadhani (Fakultas Farmasi UMI, 2023)
Irrational use of antibiotics can lead to health problems, especially bacterial resistance to antibiotics. Improper use can be affected by lack of knowledge of antibiotics use. The study aimed to examine the public knowledge level on antibiotics use in Malawili Village, Aimas District, Sorong Regency, and the influence of community characteristics on knowledge level. This research used a descriptive study with a crosssectional survey design, involving 104 respondents. The data were obtained by purposive sampling techniques using questionnaires. The research performed data analysis using univariate and bivariate with chisquare test. The results showed that the majority of respondents were indicated to have